Remembrance of the Lost Guyanese Novel: Atipa - Marc Lony (Studies in 20th & 21st Century Literature, 2002)
In 1885 the Ghio publishing house in Paris brought out Atipa, roman guyanais (Atipa: A Guianese Novel), written in Guianese Creole by an author who signed himself Alfred Parépou…
Keywords: Guianese Creole; Alfred Parépou; Atipa roman guyanais; Atipa: A Guianese Novel; French-based Creole; translation; sociocriticism; différance; French; Creole